US civil society aid & its effects on democratization in Egypt case study: the NGO Service Center project - Mesbah, Nahla Shafik (AUC Knowledge Fountain, 2009)
The last few decades have witnessed a dramatic increase in Democracy Assistance which has spurred a debate regarding the effectiveness of this type of aid in achieving Democratization in recipient countries especially in â semi-authoritarianâ settings. This thesis addresses Democracy Assistance provided to Egypt through USAID with a particular focus on civil society targeted programs. The main hypothesis of this thesis is that the failure of USAID civil society assistance to achieve Democratization, using the NGO Service Center Program as a case study, cannot be attributed alone to the nature of the political system in Egypt but that it may also be the result of (1) the narrow definition of civil society used by USAID namely equating it to non-governmental organizations mainly service NGOs while excluding HR NGOs which are critical of the Egyptian government and (2) the nature of the beneficiary Egyptian civil society organizations targeted by USAID. The findings in the context of this thesis provide substantial support to the arguments presented in the hypothesis. The USAID's narrow definition of civil society has limited the effects of Democracy Assistance especially with the exclusion of advocacy or HR NGOs which are genuinely interested in promoting the democracy agenda. Furthermore, the nature of beneficiary Egyptian NGOs, which are plagued by a variety of problems from lack of internal democracy to low interest in constituency involvement in decision making, has also proved to be detrimental to the project's ability to foster democratization. Moreover, the lack of cooperation between the various Egyptian NGOs has also negatively affected their ability to influence decision makers.